Miriam Hopkins : Life and Films of a Hollywood Rebel - Ellenberger, Allan R., 1956- (Book collections on Project MUSE., 2018)
"In the first comprehensive biography of this colorful performer, Allan R. Ellenberger illuminates Hopkins's fascinating life and legacy. Her freewheeling film career was exceptional in studio-era Hollywood, and she managed to establish herself as a top star at Paramount, RKO, Goldwyn, and Warner Bros. Over the course of five decades, Hopkins appeared in thirty-six films, forty stage plays, and countless radio programs. Later, she emerged as a pioneer of TV drama. Ellenberger also explores Hopkins's private life, including her relationships with such intellectuals as Theodore Dreiser, Dorothy Parker, Gertrude Stein, and Tennessee Williams"--